Adaptation strategies of small-scale fisheries within changing market and regulatory conditions in the EU. (February 2019) - Prosperi, Paolo; Kirwan, James; Maye, Damian; Bartolini, Fabio; Vergamini, Daniele; Brunori, Gianluca
Abstract: This paper presents an analysis of the diversification and non-productivist practices and strategies deployed by European small-scale fishers vis-à-vis contextual regulatory and market factors. Building on resilience thinking – combined with a qualitative case study approach involving primary producers and associated stakeholders – the strategies of primary producers in two specific contexts are examined: inshore fisheries in Cornwall (UK) and coastal fisheries in Tuscany (Italy). In so doing, the analysis identifies possible adaptation strategies that can help support the sustainability of the fisheries involved. The strategies adopted by fishers include, for example, investing in innovation, reorganising the supply chain, multifunctionality and diversification, and implementing environmentally friendly activities.